2023
DOI: 10.3389/fphys.2023.1107434
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of entomopathogenic fungi against fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae) under laboratory conditions

Abstract: Maize is an essential crop of China. The recent invasion of Spodoptera frugiperda, also known as fall armyworm (FAW), poses a danger to the country’s ability to maintain a sustainable level of productivity from this core crop. Entomopathogenic fungi (EPF) Metarhizium anisopliae MA, Penicillium citrinum CTD-28 and CTD-2, Cladosporium sp. BM-8, Aspergillus sp. SE-25 and SE-5, Metarhizium sp. CA-7, and Syncephalastrum racemosum SR-23 were tested to determine their effectiveness in causing mortality in second inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Of the various EPF, B. bassiana and M. anisopliae are well-known for their ability to colonize plants endophytically [11]. In general, many recent investigations stated that numerous B. bassiana and M. anisopliae isolates have shown the high efficiency of these fungi in the infection and control of S. frugiperda larvae [34][35][36][37][38]. We conducted this study to investigate the endophytic effects of two different entomopathogenic fungi, B. bassiana, and M. anisopliae, using two inoculation methods: foliar spray and seed inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…Of the various EPF, B. bassiana and M. anisopliae are well-known for their ability to colonize plants endophytically [11]. In general, many recent investigations stated that numerous B. bassiana and M. anisopliae isolates have shown the high efficiency of these fungi in the infection and control of S. frugiperda larvae [34][35][36][37][38]. We conducted this study to investigate the endophytic effects of two different entomopathogenic fungi, B. bassiana, and M. anisopliae, using two inoculation methods: foliar spray and seed inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…These include the potential for the development of resistance ( Samanta et al, 2023 ; Roy et al, 2023 ), detrimental effects on non-target organisms and beneficial insects ( Khurana et al, 2023 ; Sharma et al, 2023 ), contamination of water and soil, and potential human health hazards ( Idrees et al, 2023a ; Treviño et al, 2023 ). There is a clear need for alternative strategies that can effectively manage fall armyworm populations while minimizing adverse environmental and health impacts ( Idrees et al, 2023b ; Palli et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…BM-8, Penicillium citrinum CTD-28, and Penicillium sp. CTD-2 have demonstrated lethality in S. frugiperda larvae at rates of 54.0%, 48.0%, 44.0%, and 42.0% respectively (Idrees et al, 2023). A study conducted in South Sumatra showed that Aspergillus sp., Beauveria sp., Chaetomium sp., and Curvularia sp.…”
Section: Introductionmentioning
confidence: 99%